2021
DOI: 10.1186/s13063-021-05248-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation and chemotherapy versus chemotherapy alone for locally advanced pancreatic cancer (PELICAN): study protocol for a randomized controlled trial

Abstract: Background Approximately 80% of patients with locally advanced pancreatic cancer (LAPC) are treated with chemotherapy, of whom approximately 10% undergo a resection. Cohort studies investigating local tumor ablation with radiofrequency ablation (RFA) have reported a promising overall survival of 26–34 months when given in a multimodal setting. However, randomized controlled trials (RCTs) investigating the effect of RFA in combination with chemotherapy in patients with LAPC are lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Surgical resection was not feasible in the remaining 8 patients, because of metastatic disease ( n = 4, 20.0%) or extensive local regional tumor ingrowth from peripancreatic vasculature ( n = 4, 20.0%). From this latter group, all patients were treated with radiofrequency ablation in the setting of a clinical trial [ 38 ]. See Supplementary Digital Content 2 for surgical and pathology outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical resection was not feasible in the remaining 8 patients, because of metastatic disease ( n = 4, 20.0%) or extensive local regional tumor ingrowth from peripancreatic vasculature ( n = 4, 20.0%). From this latter group, all patients were treated with radiofrequency ablation in the setting of a clinical trial [ 38 ]. See Supplementary Digital Content 2 for surgical and pathology outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The role of tumor ablation in pancreatic cancer is still understudied and there have been no completed trials that compare multiple ablation modalities [ 115 , 117 ]. Examples of the major ongoing trials are the “Pancreatic Locally Advanced Unresectable Cancer Ablation” (PELICAN) trial [ 118 ], which is an international multicentric superiority RCT investigating the effect of RFA in combination with chemotherapy in 228 patients across 16 centers in the Netherlands and four European centers, and the CROSSFIRE trial in the Netherlands, which compares the efficacy of IRE and chemotherapy (FOLFIRINOX) to the efficacy of FOLFIRINOX and stereotactic ablative radiotherapy (SABR) in 138 patients with non-resectable, non-metastasized, locally advanced pancreatic cancer (LAPC) [ 117 ].…”
Section: Pancreatic Tumorsmentioning
confidence: 99%
“…Interestingly, a randomised controlled trial revealed a conflicting conclusion that radiofrequency ablation alone showed the lack of superiority over traditional chemotherapy, and it should only be considered a part of multimodal therapies for localised advanced PC [ 151 ]. To investigate the effect of RFA and chemotherapy against standard chemotherapy alone in PC, a current multicentre randomised clinical trial is being conducted [ 152 ]. However, to our knowledge, no randomised clinical trial comparing the outcome of RFA and surgical resection in PC has been conducted.…”
Section: Locoregional Therapiesmentioning
confidence: 99%
“…As a result, local control of the disease is the main indication of locoregional therapies. For instance, locoregional ablative therapies are introduced with other treatments when the tumour is not suitable for surgery, or in advanced stages for debulking of the tumours rather than complete tumour necrosis [ 152 ], and as consolidative treatments in stable diseases. Unfortunately, locally advanced pancreatic cancer is associated with a dismal prognosis; in this case, ablation therapies are introduced as palliative therapies [ 241 ].…”
Section: Authors’ Opinion On the Future Perspectives Of Locoregional ...mentioning
confidence: 99%